Factors Causing Breast Milk Dams in Postpartum Mothers at Ajangale Community Health Center Implementing Unit - Ismawati Ismawati; Sulfianti Sulfianti (Journal La Medihealtico, 2021)
This study employs a descriptive quantitative approach. A cross sectional design was adopted for the investigation. There are 35 samples that fit the requirements. The findings of this study indicate that 1) bivariate analysis using the chii square test yielded a p-value of 0.000 p0.05, indicating that Ha is accepted and H0 is rejected, implying that there is a relationship between breastfeeding on demand and the incidence of breast milk dam at UPT Ajangale Health Center. 2) bivariate analysis using the chii square test yielded a p-value of 0.001 and a p-value greater than 0.05. This suggests that Ha is accepted and H0 is rejected, implying that there is a correlation between breast care and the occurrence of breast milk dams at UPT Puskesmas Ajangale. 3) using bivariate analysis, the chi square test results were produced; the chi square test resulted in a p-value of 0.002 p>0.05. This indicates that there is a correlation between nursing postures and breast milk dams at UPT Puskesmas Ajangale.